Enhancing metallurgical and mechanical properties of friction stir lap welding of aluminum alloys by microstructure reconstruction - Kun Gao; Zhenlong Zhang; Guangdong Wang; Xiaojun Sun; Yingyue Zhang (Scientific Reports)
Abstract Friction stir processing (FSP) is successfully employed to alleviate their hook defects of friction stir lap welding (FSLW) of aluminum alloys. The mechanical properties and microstructural characteristics are compared and analyzed between the FSLW&FSP joint fabricated by FSLW and FSP and the FSLW joint. The microstructural analysis shows that the hook defect zone at the advancing side of the FSLW joint is changed into the overlap zone (OZ) of the FSLW&FSP joint due to microstructure reconstruction caused by performing the FSP. The heterogeneous and coarse grains at the hook defect zone of the FSLW joint are transformed into refined and equiaxed grains at the OZ of the FSLW&FSP joint as a result of dynamic recrystallization. The results of tensile tests show that tensile strength and fracture toughness of the FSLW&FSP joint are 85.7% and 220% higher compared to those of the FSLW joint, respectively. The cross sections of broken lap joints reveal that their failure location is shifted from the hook defect at AS of the FSLW joint to the thermo-mechanically affected zone of the FSP zone of FSLW&FSP joint. The combined action of effective sheet thickness increasement, microstructure uniformity, grain refinement, and local stress concentration reduction act as the strengthening mechanism of the lap joint of aluminum alloys.